Morphometry Identification of Lice on Male Javan Langur (Trachypithecus auratus) - Titisari, Nurina; Cahyaningrum, Yunita; Yesica, Reza; Rickyawan, Nofan (Jurnal Medik Veteriner, 2022)
A rehabilitation center for Javan Lutung animals in East Java carries out routine checks on rehabilitated animals to prevent diseases that can affect health. Diseases that can infect these endangered animals are not only diseases that are inside the body but also outside the body such as lice infestation. The purpose of this study was to identify the species of louse that attack Javan langurs in an effort to increase information on ectoparasite species in these endemic animals. The sample was obtained from an adult Javan langur, then the sample was preserved by the unstained Slide mounting method. The results were observed using a microscope and body length was measured using the ImageJ software. The results showed that the ectoparasite shape has a flat-dorsoventral body with a total body length of 1.65 mm. From morphometry and morphological characteristics, the samples identified were the male species of Pedicinus ancoratus.